Talvadaksen joikuperinne : etnomusikologinen perustutkimus tenonsaamelaisten musiikista - Kantola, Tuula; Turun yliopisto. Kulttuurien tutkimuksen laitos; Turun yliopiston offsetpaino (Turku : [Turun yliopisto], 1984)
Summary.
Keywords: Folk music -- Finland -- Utsjoki -- History and criticism; Sami (European people) -- Finland -- Music -- History and criticism; Yoiks -- Finland -- Utsjoki -- History and criticism; joiut; saamelaiset; etnomusikologia; melodiat; Utsjoki; Talvadas